2022
DOI: 10.1111/cch.12996
|View full text |Cite
|
Sign up to set email alerts
|

Life under lockdown for children with autism spectrum disorder: Insights from families in South Africa

Abstract: Background: Children with Autism Spectrum Disorder (ASD) remain vulnerable during the Covid-19 outbreak due to significant changes to their daily routines, social interactions and diets. In addition, these challenges may be exacerbated for children living in low-and middle-income countries (LMIC) such as South Africa where there are already barriers such as poverty, access to resources and availability of support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The authors concluded that the long-term lockdown restrictions meant that parents had more time for family activities. A similar finding was also reported in a small South African study, where increased interactions and emotional attachment with siblings had a positive effect on children with ASD [36].…”
Section: Discussionsupporting
confidence: 87%
“…The authors concluded that the long-term lockdown restrictions meant that parents had more time for family activities. A similar finding was also reported in a small South African study, where increased interactions and emotional attachment with siblings had a positive effect on children with ASD [36].…”
Section: Discussionsupporting
confidence: 87%
“…Our approach highlights the utility of leveraging brief, naturalistic home-based approaches, which minimize demands on families. This point is salient in the context of the COVID-19 pandemic, which precipitated a new “normal” centered on virtual encounters, with some parents preferring online assessments or services for pediatrician visits 73 or parenting support 74 , 75 . Indeed, an important takeaway from this study is the high rate of acceptability from parents for uploading recorded samples of interactions between themselves and their children.…”
Section: Discussionmentioning
confidence: 99%
“…A common feature of children with ASD is a strict follow up with their schedule, and disruption of their routines can cause them significant distress [ 46 ]. Due to this, individuals with ASD are particularly impacted by the COVID-19 pandemic [ 10 , 47 , 48 ]. Adapting to new daily routines, environmental changes, and uncertainty related to the pandemic have been determined to be causing distress in children with ASD, worsening both the core features of ASD and their overall mental health [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%